Tracking Antigen Expression of Toxoplasma gondii in Mice by Immuno (Cyto) Histochemistry - Ida Ayu Pasti Apsari; Ida Bagus Oka Winaya; Tjokorda Sari Nindhia; Ida Bagus Ngurah Swacita (Institute for Research and Community Service, Udayana University, 2017)
Mouse has been an animal model that is very sensitive towards the Toxoplasma gondii infection. This research infects 30 mice with free-range chicken heart inoculate and the detection of T. gondiiby immunohistochemistry on the infected mice. The purpose of this study is to track T.gondii antigen expression by immune(cyto)histochemistry in mice. Observation over mice was conducted over 10 weeks. After 10 weeks, the mice are examined for its peritoneal fluid by microscopic and immunohistochemistry examination. Continued by the examination of internal organs to track the expression of T.gondii antigens by immunohistochemistry. The study result showed microscopic examinations on peritoneal fluid did not found any cyst or tachyzoites form of T.gondii. Examination of peritoneal fluid by immunohistochemistry was found to detect expressions of T.gondii antigen. Examinations of the mice’s internal organs detected expressions of T.gondii antigen only in the brain by immunohistochemistry examinations.